Play Therapy in Family Education - Demydenko, Tetiana (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Taking into account growing scientific interest in pedagogic of domestic education to methodologies of playing therapy, their orientation on adjusting of the lost emotional connections between a child and adults, high potential of opening of creative capabilities of participants, increase of their self-appraisal, confidence in own forces, possibilities of organization of effective co-operation, collaboration, work of adults and children, in the article the problem of the use of playing therapy is examined in domestic education, socio-pedagogical help to the parents in organization of playing co-operating with a child. The article analyzes the game as the leading activity of the child, its features and functions, pedagogical (educational) potential therapeutic possibilities conceptualized games in family education, highlights the problem of the use of play therapy to harmonize parent-child relationship. Determined psychotherapeutic co-op nature of children and parents, investigate the position's parents. Taking into account it, actual is socio-pedagogical support of playing co-operation of parents and children. The interesting form of her organization – playing attraction, in that can participate social teachers, children and parents, is analyzed.